Raksa raya Malaysia - Ahmad Zaharuddin Sani Ahmad Sabri; Institut Pemikiran Tun Dr. Mahathir Mohamad (Kuala Lumpur : Institut Terjemahan & Buku Malaysia, 2014)
On Malaysian history and political governmental in Malaysia.
Keywords: Malaysia -- History; Malaysia -- Politics and government; Malaysia -- Constitution